2016
DOI: 10.1097/md.0000000000005330
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced breast magnetic resonance imaging for the prediction of early and late recurrences in breast cancer

Abstract: The aim of the study was to evaluate dynamic contrast-enhanced breast magnetic resonance imaging (DCE-MRI) features for the prediction of early and late recurrences in patients with breast cancer.Of 1030 breast cancer patients who underwent surgery at our hospital from January 2007 to July 2011, 83 recurrent breast cancer patients were enrolled in this study. We compared MRI features (background parenchymal enhancement [BPE], internal enhancement, adjacent vessel sign, whole-breast vascularity, initial enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
(35 reference statements)
0
24
0
7
Order By: Relevance
“…Also, increased vascularity always showed significant association with disease recurrence in every multivariable model. Increased vascularity due to the tumor can affect other MRI parameters related to tumor vascularity, including perfusion or texture parameters 13,19 . However, texture and perfusion parameters were associated with disease recurrence independent of increased ipsilateral vascularity in present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, increased vascularity always showed significant association with disease recurrence in every multivariable model. Increased vascularity due to the tumor can affect other MRI parameters related to tumor vascularity, including perfusion or texture parameters 13,19 . However, texture and perfusion parameters were associated with disease recurrence independent of increased ipsilateral vascularity in present study.…”
Section: Discussionmentioning
confidence: 99%
“…Breast MRI is performed in most patients with newly diagnosed breast cancer and can both diagnose breast cancer accurately and predict cancer prognosis using variable imaging features. Previous studies identified that several imaging features including rim enhancement pattern of tumor 13,14 , presence of peritumoral edema on T2-weighted image 15,16 , higher degree of background parenchymal enhancement (BPE), and increased vascularity around the tumor, indicate poor prognosis in breast cancer [13][14][15][16][17] . In addition to morphologic features of tumor, quantitative MRI parameters derived from advanced MR techniques have been recently developed for prediction of breast cancer prognosis.…”
mentioning
confidence: 99%
“…Nonmass enhancement was defined as the enhancement of an area that was not a mass, whose internal enhancement characteristics were discrete from the normal surrounding breast parenchyma. In addition, the presence of peritumoral edema and the pattern of tumor shrinkage (concentric or nonconcentric) were also evaluated because these findings have been reported to show an association with LRR (17,(22)(23)(24) or distant metastasis (25). The presence of peritumoral edema was defined when high signal intensity around the tumor or posterior to the tumor mass in the prepectoral area was observed on T2-weighted images (26).…”
Section: Clinical-pathologic and Mr Image Feature Analysismentioning
confidence: 99%
“…Contrast-enhanced breast magnetic resonance imaging (MRI) is an ideal imaging modality that helps in representing tumour angiogenesis. In MRI, the contrast enhanced pattern of the tumour correlates to the micro-vessels density which is a characteristic of tumour angiogenesis [8]. The features of dynamic contrast-enhanced MRI (DCE-MRI) such as washout curve type, peripheral rim enhancement, and faster enhancement are correlated with overall survival and recurrence of breast cancer patients [8].…”
Section: Introductionmentioning
confidence: 99%